Narrativas de enfermeiras e enfermeiros em tempos da COVID-19: uma história oral - Gabrielli Pinho de Rezende (2022)
COVID-19 is a disease known in China at the end of 2019. It becomes a pandemic and changes the lives of all people. With high transmissibility, considerable mortality, and a general picture of uncertainties regarding its development, all countries started to be organized as much as possible. In the area of health, while institutions and professionals undergo structuring to organize their services, we found existing problems such as fragmented relationships at work, overload, the precariousness of resources, the lack of support for workers' health, among other weaknesses. Professional nurses, known for their proximity to patients and constant care, are inserted in this scenario and are experiencing personal and professional transformations. Thus, we ask how the history of the pandemic - COVID-19 - has been built in the daily life of Brazilian nurses? How do you establish, personally and professionally, your history as a nurse in this moment of great historical, social, and economic relevance for the world population? This study aims to understand the history of nurses working during the COVID-19 pandemic and their personal and professional experiences. This research has a qualitative approach, with 30 nurses working on the front line of the fight against COVID-19 in different Brazilian states. Data collection took place through an interview with a semi-structured script, through open access virtual communication platforms. Oral History was used as a methodological reference and, the Comprehensive Sociology of Everyday Life proposed by Michel Maffesoli was used as a theoretical reference. The analysis of the interviews allowed the construction of three categories for discussion: 1. This is how the story begins: Vivid Moments; 2. Experiencing the Pandemic: Nurses Confronting COVID-19; 3. What do we still have to experience: expectations, end, beginning? We could understand that the history of nurses working on the front line of the pandemic was built, and still is, in an unstable political, social, and economic context and uncertainties that brought new ways of working, caring, and being. Life before COVID-19 showed work with a historical burden of devaluation, search for better wages, and overload, but it was possible to have contact with family and friends and carry out leisure activities. With the pandemic, all areas were taken by economic, political, and social uncertainties; in the information that was conveyed and consequently on how to act in the context of health. The problems already experienced by nursing are reaffirmed, in addition to changes in flows and protocols, weaknesses such as the unavailability of personal protective equipment, the illness and death of colleagues, the need to address the health of workers and to recognize the nurse as a human being. The reality of work was characterized by the reaffirmation of overload, inequality, and devaluation; by daily changes in flows, audiences, services, and protocols; due to uncertainties and weaknesses in the availability of personal protective equipment and the illness and death of acquaintances and co-workers. This whole situation showed the fragility of workers' health care, the need to reinvent the practice of nursing, and the view of the nurse as a human being who has weaknesses. With so many difficulties, the mission of caring and the desire to play their role as a professional motivated the continuity of care at this historic moment. The study collaborators had as expectations regarding the experience of the pandemic a greater appreciation of nursing and knowledge based on science, better working conditions and assistance to workers, the production of vaccines and minimization of the crisis, the improvement of technology as a tool for work and the transformation of people and their values. We expect that COVID-19 and the results of this study will not only awaken the need for changes in the health system but also a differentiated look at nursing professionals.